Unipolar pole piece, battery cell, preparation methods of unipolar pole piece and battery cell, and secondary battery

By using a combination technology of foam current collector and ceramic ionic liquid retention layer in lithium batteries, the problem of SOC inhomogeneity caused by the increase of electrode thickness is solved, and a high-speed thick electrode battery structure with high energy density and cycling stability is achieved.

CN119447184APending Publication Date: 2025-02-14福建龙净储能电池有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411352441.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the process of increasing the energy density of existing lithium batteries, the increase in electrode thickness leads to uneven migration of electrons and ions in the electrode active material layer, resulting in SOC inhomogeneity, which in turn affects the cycle stability and energy density of the battery.

Method used

Using foam current collector as the base material to form a composite liquid collector, and an ionic liquid retention layer containing ceramic material is formed on its surface. By stacking it, the uniformity of ions transport in the thickness direction is ensured, and the customizable electrode thickness is achieved. change.

Benefits of technology

Customization of electrode thickness is achieved, the uniformity of SOC is ensured, the energy density and cycle stability of the battery are improved, and a high-speed thick electrode battery structure is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447184A_ABST
    Figure CN119447184A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and provides a unipolar pole piece, a battery cell, preparation methods of the unipolar pole piece and the battery cell, and a secondary battery. The single-stage electrode comprises a composite current collector and an ion liquid retention layer positioned on the surface of the composite current collector; wherein the composite current collector comprises a foam current collector and an electrode coating distributed in holes of the foam current collector, the electrode coating contains an electrode active material, and the ion liquid retention layer contains a ceramic material. A battery cell formed by stacking the unipolar electrodes has SOC uniformity in the thickness direction of the electrodes, and a high-rate thick electrode battery structure can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of batteries, and specifically provides a unipolar pole piece and a preparation method thereof, a battery cell and a preparation method thereof, and a secondary battery. Background Art

[0002] Secondary batteries may include lithium-ion batteries, sodium-ion batteries, etc., and their general core components include positive electrodes, electrolytes, separators, and negative electrodes, and the preparation processes include assembly, tank liquid, and formation. During assembly, generally, the positive electrode, separator, negative electrode, and separator are used as the smallest repeating unit to form a battery cell by winding or stacking, and the battery cell is placed in a casing, and then filled with electrolyte, and then charged and activated after packaging. Taking lithium-ion batteries as an example, the capacity is determined by the amount of positive electrode active material (i.e., lithium source). In other words, under the condition that the space and total weight remain unchanged, the more positive electrode active material, the greater the energy density of the battery. Secondary batteries have undergone many years of development, and the world has been working hard to improve battery energy density to reduce costs. The energy density of mass-produced lithium batteries is currently 350Wh / kg, which almost reaches the limit of energy density.

[0003] The main traditional methods to improve the energy density of lithium batteries include: 1) selecting a high-capacity material system; 2) designing a high-voltage electrolyte; 3) optimizing the formula of the positive and negative electrode slurry to increase the proportion of active materials in the electrode; 4) using a thinner current collector to reduce its proportion; 5) increasing the coating amount of the positive and negative electrodes to increase the proportion of active materials in the electrode; 6) reducing the amount of electrolyte to increase the specific energy of the battery; 7) optimizing the battery structure to reduce the proportion of the tabs, packaging materials, etc. in the battery. Among them, method 5) is the most common and easiest to implement. Usually, the surface density of the positive and negative electrode coating can be increased by simply increasing the gap of the coater or increasing the flow rate. The increase in the surface density of the positive and negative electrodes means that the coating amount of the single-layer positive and negative electrodes increases, and the number of core positive and negative electrode layers of the same volume is small, and the corresponding number of current collectors and diaphragm layers is small. As a result, the total proportion of the positive and negative electrode active materials increases, and the energy density increases. However, after the electrode thickness increases, the migration and mass transfer of path electrons and ions in the positive and negative electrode active material layers also become more difficult.

[0004] Due to limited mass transfer problems, severe SOC non-uniformity occurs along the thickness of the thick electrode; the top area of ​​the electrode mainly undergoes electrochemical reactions, while the bottom area does not participate in the electrode reaction. That is to say, at a certain current density, in the later stage of the cycle, the top layer of the thick electrode may gradually be exposed to a higher effective current density, and the lithium gradient inside the particles rises sharply, which can produce a large stress field inside the particles (such as the formation of microcracks or irreversible local phase transitions), which in turn causes the particles to break, produce new exposed surfaces, and continue to produce a thick organic surface layer. These side reactions gradually occur on the material and cause battery degradation, and the battery cannot be made thicker. Summary of the invention

[0005] In view of the above problems existing in the prior art, the purpose of the present application is to provide a monopolar electrode, a battery cell and their respective preparation methods and a secondary battery. The battery cell made by stacking the monopolar electrodes has SOC uniformity along the thickness direction, and can obtain a high-rate thick electrode battery structure.

[0006] In a first aspect, the present application provides a unipolar electrode, which is a positive electrode or a negative electrode. The unipolar electrode comprises a composite current collector and an ion liquid retaining layer located on the surface of the composite current collector; wherein the composite current collector comprises a foam current collector and an electrode coating distributed in the pores of the foam current collector, the electrode coating contains an electrode active substance, and the ion liquid retaining layer contains a ceramic material.

[0007] The unipolar electrode of the present application uses a foam current collector as a substrate, and an electrode coating containing electrode active materials is formed in its pores; compared with the use of a solid current collector without pores (such as aluminum foil, copper foil), the present application successfully breaks through the thickness limit of the conductive film layer, which can only be 20 to 30 μm at most, and the electrode coating is "filled" in the pores, so that the current collector and the conductive coating are almost at the same thickness, overcoming the unevenness of the migration of path electrons and ions in the positive and negative electrode active material layers. Furthermore, an ion liquid-retaining layer containing ceramic materials is formed on the surface of the foam current collector, so that when the unipolar pole piece is stacked as a basic unit to form a thick electrode, the uniformity of ion transmission in the thickness direction is ensured. Therefore, the unipolar pole piece of the present application with the above structure can realize the customization of the electrode thickness and obtain a high-rate battery.

[0008] In some embodiments of the present application, the thickness of the ion liquid-retaining layer is 1 to 10 μm.

[0009] In some embodiments of the present application, in the ion liquid retaining layer, the ceramic material is selected from one or more of alumina, boehmite, barium titanate and lithium aluminate.

[0010] In some embodiments of the present application, the ion liquid retaining layer further comprises a conductive agent and a binder, and the mass ratio of the ceramic material, the conductive agent and the binder is 10:(3-8):(2-6). In this way, the subsequent liquid absorption performance of the battery can be further improved.

[0011] In some embodiments of the present application, the pore size of the foam current collector is 0.001 to 0.1 mm.

[0012] In some embodiments of the present application, the porosity of the foam current collector is 10% to 95%. Further, the porosity of the foam current collector is 50% to 90%.

[0013] In some embodiments of the present application, the thickness of the foam current collector is 0.05 to 0.3 mm.

[0014] In some embodiments of the present application, the electrode coating is formed by dipping the foam current collector with an electrode slurry containing the electrode active material and drying the electrode slurry. The dipping method can make the electrode slurry fill the entire pores and improve the mass transfer effect.

[0015] Furthermore, the electrode slurry also contains a conductive agent, a binder and an optional dispersant.

[0016] In some embodiments of the present application, the monopolar electrode is a positive electrode. Accordingly, the foam current collector is a positive current collector, the electrode active material is a positive active material, and the electrode coating is a positive coating.

[0017] Furthermore, the foam current collector is foam aluminum.

[0018] Furthermore, the electrode active material is selected from at least one of lithium iron phosphate, lithium iron manganese phosphate and lithium nickel cobalt manganese oxide.

[0019] Furthermore, the surface density of the electrode coating is 200 to 420 g / m 2 .

[0020] In some embodiments of the present application, the monopolar electrode is a negative electrode. Accordingly, the foam current collector is a negative current collector, the electrode active material is a negative active material, and the electrode coating is a negative coating.

[0021] Furthermore, the foam current collector is foam copper.

[0022] Furthermore, the electrode active material is selected from at least one of graphite, hard carbon and lithium titanate.

[0023] Furthermore, the surface density of the electrode coating is 100 to 220 g / m 2 .

[0024] In some embodiments of the present application, the monopolar electrode is divided into a pole ear region and a material distribution region, wherein the pole ear region has a pole ear, and the material distribution region has the electrode coating and the ion liquid retention layer.

[0025] In a second aspect, the present application provides a method for the monopolar electrode, which comprises: applying an electrode slurry containing an electrode active substance onto a foam current collector so that the pores of the foam current collector are filled with the electrode slurry to form an electrode coating; applying a ceramic slurry containing the ceramic material on the surface of the current collector forming the electrode coating to form an ion retention layer.

[0026] In some embodiments of the present application, the method includes the following process flow:

[0027] The foam current collector is sent to the electrode slurry for dipping by a dip coating machine, and the current collector dipped with the electrode slurry is sent to an oven for drying and rolling to obtain a composite current collector;

[0028] The ceramic slurry is coated on the surface of the composite current collector by a micro-concave roll coater, and then dried to form an ion liquid retaining layer.

[0029] In some embodiments of the present application, the method further includes: before applying the electrode slurry, covering one end of the foam current collector with adhesive tape to divide the foam current collector into a tab reserved area covered by the adhesive tape and an area to be laid; after forming the ion liquid retaining layer, removing the adhesive tape and die-cutting the tab reserved area to form tabs arranged at intervals.

[0030] In a third aspect, the present application provides a battery cell comprising a positive electrode group, a negative electrode group and a separator, wherein the positive electrode group and the negative electrode group are arranged opposite to each other and respectively comprise a plurality of stacked single-polarity pole pieces, and adjacent single-polarity pole pieces are separated by an ion-retaining layer; the outer peripheries of the positive electrode group and the negative electrode group are respectively wrapped with the separator; wherein the single-polarity pole pieces are the single-polarity pole pieces described in the first aspect of the present application.

[0031] The battery cell of the present application is assembled based on a single-stage pole piece. Specifically, the battery cell has a simple sandwich structure, and the positive electrode of the present application is repeatedly stacked to form a positive electrode group of a set thickness, and the negative electrode of the present application is repeatedly stacked to form a negative electrode group of a set thickness, thereby forming a special stacked core structure, which can replace the traditional battery stacked core structure, save the number of current collectors and diaphragm layers, effectively improve the energy density, and obtain a high-rate battery.

[0032] In some embodiments of the present application, the number of positive electrodes in the positive electrode group is n1, 1<n1<272, and the number of negative electrodes in the negative electrode group is n2, 1<n2<270.

[0033] In a fourth aspect, the present application provides a method for preparing the battery cell according to the third aspect of the present application, comprising:

[0034] Stacking and hot pressing: The single-polarity pole pieces are stacked by lamination and hot-pressed to form positive and negative electrode groups respectively;

[0035] Separator coating: coating the outer periphery of the positive electrode group and the negative electrode group with a layer of separator respectively;

[0036] Core hot pressing: The positive electrode group coated with the separator and the negative electrode group coated with the separator are stacked and hot pressed.

[0037] In a fifth aspect, the present application provides a secondary battery, comprising the battery cell described in the third aspect of the present application.

[0038] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0040] Figure 1 This is a schematic diagram of a single-polarity pole piece structure in some implementation modes of the present application;

[0041] Figure 2 Schematic diagram of the composite current collector structure of some embodiments of the present application;

[0042] Figure 3 This is a schematic diagram of the electrode group structure of some embodiments of the present application;

[0043] Figure 4 Schematic diagrams of the battery cell structures of some embodiments of the present application, wherein (a) is a schematic diagram of the internal structure, and (b) is a schematic diagram of the external structure;

[0044] Figure 5 This is a schematic diagram of an existing lithium battery stack structure, with the left side being an internal schematic diagram and the right side being an external schematic diagram;

[0045] Figure 6 to Figure 8 Schematic diagram of the process flow for preparing unipolar pole pieces according to some embodiments of the present application.

[0046] Description of Reference Numerals

[0047] 200: unipolar pole piece; 11: composite current collector; 12: ion liquid retaining layer; 110: foam current collector; 111: electrode coating; 100: battery cell; 10: negative electrode group; 20: positive electrode group; 30: separator; 1: electrode slurry; 2: foam metal; 3: coating; 4: oven; 5: air nozzle; 6: hot air; 7: extrusion roller; 8: driven roller; 9: active roller; 10: material transfer device; 1a: negative pole piece; 2a: positive pole piece. DETAILED DESCRIPTION

[0048] The following describes the implementation of the present application in detail. The implementation described below is exemplary and is only used to explain the present application, and cannot be understood as limiting the present application.

[0049] The "range" disclosed in the present application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form an unclearly recorded range, and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0050] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0051] In traditional lithium-ion batteries, the main supply of electrons and lithium ions to the electrodes occurs at the electrode / current collector interface and the electrode / electrolyte interface, respectively, so there is a clear spatial distribution at the reaction front. Under conditions of ion transport limitation, the utilization rate of the active electrode material particles close to the current collector for electrochemical reactions is lower, and the path for lithium ions to diffuse from the electrode / electrolyte interface is the longest; at the electrode / electrolyte interface (i.e., the top layer of the electrode), at high current density, a sufficiently fast supply of lithium ions and electrons can be achieved, while in extreme cases, the bottom electrode may still be idle (unreacted); for electron transport limitation, the opposite is true. Therefore, in order to obtain electrodes with customizable thickness, the mass transfer effect of charge carriers must be solved first.

[0052] To this end, the first aspect of the present application provides a monopolar electrode. As some embodiments, Figure 1 and Figure 2 As shown, the monopolar electrode 200 includes a composite current collector 11 and an ion liquid retaining layer 12, wherein the composite current collector 11 includes a first surface and a second surface arranged opposite to each other along the thickness direction X of the monopolar electrode 200, the ion liquid retaining layer 12 is located on the first surface, and the composite current collector 11 includes a foam current collector 110 and an electrode coating 111 located in the pores thereof.

[0053] In the present application, the ion liquid retaining layer is a ceramic layer comprising ceramic material. Compared with ordinary polymer membranes such as PP and PE membranes, the ceramic layer has a higher liquid absorption capacity.

[0054] In some embodiments, the ceramic material is selected from one or more of aluminum oxide (Al2O3), boehmite (γ-AlOOH), barium titanate (BaTiO2) and lithium aluminate (LiAlO2). Preferably, the ceramic material is aluminum oxide and lithium aluminate, and the mass ratio of the two is 10: (2-5), for example, 10: 2, 10: 3, 10: 4, 10: 5, etc.

[0055] In some embodiments, the ion liquid retaining layer further contains a conductive agent and a binder. The introduction of the conductive agent can improve the subsequent liquid absorption and liquid retention performance of the battery, and the binder can play a role in bonding the ceramic material and the conductive agent.

[0056] In the ion retaining layer, specific examples of the conductive agent include, but are not limited to, one or more of carbon nanotubes (CNT), conductive carbon black (Super-P), carbon nanofibers (VGCF), acetylene black (AB), graphene and furnace black.

[0057] In the ion-retaining layer, specific examples of the binder include, but are not limited to, polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polymethyl methacrylate (PMMA), polyethylene oxide (PEO), phenolic resin (PF), polyimide (PI), polyvinylidene fluoride (PVDF), and the like.

[0058] The mass ratio of the ceramic material, the conductive agent and the binder may be 10:(3-8):(2-6), for example, 10:3:2.

[0059] In some embodiments, the ion liquid retaining layer can be formed by coating a ceramic slurry on the surface of a current collector and drying it. The ceramic slurry can be formed by uniformly dispersing the ceramic material, the conductive agent, and the binder in a solvent. Specific examples of the solvent include, but are not limited to, N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), tetrahydrofuran (THF), ethanol (EtOH), acetone (ACE), and the like.

[0060] Generally, when the battery is charged, ions are separated from the positive electrode, and enter the negative electrode through the electrolyte through the diaphragm. If the negative electrode film layer is thicker, in addition to reacting with the surface of the negative electrode, the lithium ions must also penetrate the negative electrode to reach the depth direction, which will form an ion concentration difference. The higher the thickness, the greater the concentration difference, resulting in concentration polarization. Concentration polarization will cause the anode to be more positive and the cathode to be more negative. The battery reaches the cut-off voltage prematurely, causing "virtual electricity". The present application sets the ion liquid retention layer on the surface of the current collector so that when a thick electrode (i.e., an electrode group) is formed by stacking unipolar electrodes, the ion diffusion distance can be kept consistent with the active material. When the battery is charged, when lithium ions are transmitted from the positive electrode through the electrolyte and penetrate into the negative electrode area, the ion liquid retention layer at every distance plays a role in replenishing lithium because the electrode plates are stacked. In this way, the concentration difference can be eliminated, so that the ion conduction speed is not limited.

[0061] In some embodiments, the thickness of the ion liquid retaining layer may be 1 to 10 μm, such as 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, etc. Preferably, the thickness of the ion liquid retaining layer is 3 to 8 μm. Thus, the space occupancy of the stacked battery cells can be reduced while improving the liquid absorption and liquid retention effects.

[0062] In the present application, the composite current collector includes a foam current collector and an electrode coating located in its pores. Compared with a solid current collector without pores, the foam current collector has a three-dimensional space and a very large specific surface area, so that it has a large contact area with the active material, and the electrode coating is distributed in the pores, which can promote the rapid conduction of electrons between the active material and the current collector without dead angles, and the electron conduction will not become difficult as the thickness of the electrode increases. During high-rate charge and discharge, the electrochemical reaction is fast and easy, so that the rate performance of the thick electrode battery is effectively improved. In addition, the foam current collector can usually be a foam metal with a honeycomb mesh inside.

[0063] In some embodiments, the porosity of the foam current collector may be 10% to 95%, such as 20%, 60%, 80%, 90%, etc. Preferably, the porosity of the foam current collector is 50% to 90%. Thus, the current collector can have a higher strength while increasing the content of active substances.

[0064] In some embodiments, the thickness of the foam current collector may be 0.05-0.3 mm, such as 0.1 mm, 0.2 mm, 0.3 mm, etc. In order to further reduce the effective distance of ion mass transfer, the thickness of the foam current collector is preferably 0.1-0.2 mm.

[0065] In the present application, the unipolar pole piece may be a positive pole piece or a negative pole piece. Accordingly, the components in the foam current collector and the electrode coating may be selected according to the electrode type. This is described below.

[0066] [Positive electrode]

[0067] In the positive electrode sheet, the foam current collector is a positive electrode foam current collector, the electrode active material is a positive electrode active material, and the electrode coating is a positive electrode coating.

[0068] In the present application, the positive electrode foam collector can be selected from various common positive electrode foam metals for lithium batteries, such as aluminum, aluminum alloy, nickel, titanium, etc.

[0069] In some embodiments, the positive electrode foam current collector is foamed aluminum.

[0070] In the present application, the positive electrode active material may be a lithium battery active material, and may be specifically selected from various commonly used lithium battery positive electrode active materials, such as lithium phosphates with an olivine structure, lithium transition metal oxides, etc. Specific examples of the positive electrode active material include, but are not limited to, lithium iron phosphate (LiFePO4, referred to as LFP), lithium iron manganese phosphate, lithium nickel oxide (such as LiNiO2), lithium cobalt oxide (such as LiCoO2), lithium manganese oxide (such as LiMnO2), and lithium nickel cobalt manganese oxide (such as NCM811). Preferably, the positive electrode active material is at least one of lithium iron phosphate, lithium iron manganese phosphate and lithium nickel cobalt manganese oxide.

[0071] In some embodiments, the positive electrode coating further contains a conductive agent and a binder. The conductive agent may be selected from at least one of carbon nanotubes, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots and carbon nanofibers. The binder may be selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and the like. Optionally, the positive electrode coating further contains a dispersant, such as sodium carboxymethyl cellulose (CMC).

[0072] As some examples, the positive electrode coating may be formed by dipping the positive electrode slurry including the positive electrode active material, the conductive agent, the binder and the dispersant into the foam current collector and drying the positive electrode slurry, wherein the solvent used in the positive electrode slurry may be NMP, and the viscosity of the positive electrode slurry may be controlled between 10,000 and 100,000 mPa·s.

[0073] In some embodiments, the mass content of the positive electrode active material in the positive electrode coating is greater than 95%.

[0074] In the present application, the surface density of the positive electrode coating can be set according to the required battery specifications. In some embodiments, the surface density of the positive electrode coating is 200 to 420 g / m 2 , for example 230g / m 2 , 250g / m 2 , 330g / m 2, 340g / m 2 , 380g / m 2 Preferably, the surface density of the positive electrode coating is 260-340 g / m 2 .

[0075] [Negative electrode]

[0076] In the negative electrode sheet, the foam current collector is a negative electrode foam current collector, the electrode active material is a negative electrode active material, and the electrode coating is a negative electrode coating.

[0077] In the present application, the negative electrode foam current collector can be selected from various common negative electrode metal foam current collectors for lithium batteries, wherein the metal is, for example, copper, copper alloy, nickel, nickel alloy, etc.

[0078] In some embodiments, the negative electrode foam current collector is foamed copper.

[0079] In the present application, the negative electrode active material may be a negative electrode active material for a lithium battery, such as graphite, hard carbon, lithium titanate, and the like.

[0080] In some embodiments, the negative electrode coating further contains a conductive agent and a binder. Wherein, the conductive agent can be selected from at least one of superconducting carbon black, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers. The binder can be at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA). Optionally, the negative electrode coating further contains a dispersant, such as sodium carboxymethyl cellulose (CMC).

[0081] As some examples, the negative electrode coating can be formed by dipping the negative electrode slurry containing the negative electrode active material, the conductive agent, the binder and the dispersant into the foam current collector and drying the negative electrode slurry. The solvent used in the negative electrode slurry can be water, and the viscosity of the negative electrode slurry can be controlled between 20,000 and 200,000 mPa·s.

[0082] In the present application, the surface density of the negative electrode coating can be set according to the surface density of the positive electrode and the negative electrode excess coefficient. In some embodiments, the surface density of the negative electrode coating can be 100 to 220 g / m 2 , for example 100g / m 2 , 120g / m 2 , 150g / m 2 , 140g / m 2 , 160g / m 2 , 170g / m 2 , 200g / m 2 etc., preferably 120 to 170 g / m2 .

[0083] In the present application, the monopolar electrode may be provided with a tab or may not have a tab, and may be welded in subsequent use. In some embodiments, the tab is provided by a foam current collector, for example, formed by die-cutting the current collector. Thus, the monopolar electrode is divided into a tab region and a fabric region, wherein the tab region is the tab, and the fabric region has the electrode coating and the ion liquid retaining layer.

[0084] The second aspect of the present application provides a method for preparing the monopolar pole piece, which comprises: applying an electrode slurry (positive electrode slurry or negative electrode slurry) containing an electrode active material onto a foam current collector so that the pores of the foam current collector are filled with the electrode slurry, and forming an electrode coating after drying; applying a ceramic slurry containing the ceramic material on the surface of the current collector, and forming an ion liquid retention layer after drying.

[0085] In order to mass-produce unipolar pole pieces, according to some embodiments, the method includes the following process flow: using a dip coating machine to deliver the foam current collector to the electrode slurry for dip coating, and conveying the current collector dipped in the slurry to an oven for drying and rolling to form an electrode coating to obtain a composite current collector; using a micro-concave roller coater to coat the ceramic slurry on the surface of the composite current collector, and after drying, forming an ion liquid retention layer.

[0086] In some embodiments, the method further includes: before applying (e.g., dipping) the electrode slurry, covering one end of the foam current collector with adhesive tape to divide the foam current collector into a tab reserved area covered by the adhesive tape and a waiting area for material distribution, wherein the waiting area for material distribution is used to form the electrode coating and the ion liquid retention layer; after forming the ion liquid retention layer, removing the adhesive tape and die-cutting the tab reserved area to form tabs arranged at intervals.

[0087] According to a specific implementation mode, Figure 6As shown, the foam metal 2 is transported to the electrode slurry 1 at a certain angle and speed, and the foam metal 2 is coated by dipping so that the slurry enters the metal pores. The current collector dipped in the slurry is conveyed along the height direction (such as the vertical direction) and passes through the oven 4. The oven 4 is provided with a nozzle 5 in the height direction to blow out hot air 6 to dry the slurry and form a coating 3. In this process, the driven roller 8 is used for guiding, the active roller 9 is used to drive the conveyor, and the squeezing roller 7 is rotated and squeezed in the opposite direction of the conveyor to compact the material layer and remove excess slurry. In order to increase the baking distance, the current collector can pass through the active roller 9 multiple times to form an S-shaped path. It is preferred to select the thickness of the foam metal 2 according to the thickness after compaction to ensure that the thickness of the pole piece after rolling does not exceed the thickness of the foam metal 2 itself (thickness of the foam metal = pole piece surface density / pole piece compaction density). A micro-concave roller coater is used to coat ceramic slurry on one surface of the rolled electrode, and an ion liquid retaining layer of the required thickness is obtained through multi-section oven baking to form an electrode coating-ion liquid retaining layer basic unit.

[0088] Furthermore, the unipolar pole piece is also provided with a pole ear, which is formed by die-cutting the current collector. In this case, before dip coating, a blank foil (i.e., the pole ear reserved area) is reserved on one side of the foam metal, and the other side (the area to be coated) is dip coated. Figure 7 As shown, the foam metal is pretreated before dip coating: the area (edge) where the foil needs to be left blank is covered with adhesive tape, and then dip coating is performed. After dip coating, before drying in the oven 4, the foam metal is removed by the material removal device 10. The material removal method includes but is not limited to: air flow purging, high vacuum suction, and ultrasonic stripping. It is preferred to use high vacuum suction to remove all kinds of slurries on the adhesive tape covered area. In addition, after the ion liquid retaining layer is formed, the adhesive tape is torn off to form an electrode coating-ion liquid retaining layer basic unit with a reserved area for the pole ear.

[0089] Furthermore, the process flow also includes: sequentially slitting, die-cutting and cutting the current collector having the electrode coating and the ion liquid retaining layer,

[0090] Cutting: Cut the pole piece into pole pieces of designed width;

[0091] Die cutting: Use laser to die cut the cut pole pieces into spaced pole ears;

[0092] Cutting: Cut the pole pieces into single pieces to facilitate flexible stacking to obtain cores of different specifications.

[0093] A third aspect of the present application provides a battery cell. According to some embodiments, Figure 4As shown, the battery cell 100 includes a positive electrode group 20, a negative electrode group 10 and a separator 30 coated on the periphery of each electrode group. Among them, the positive electrode group 20 is formed by repeatedly stacking the positive electrodes of the present application, and the adjacent positive electrodes are separated by an ion liquid retaining layer, and the negative electrode group 20 is formed by repeatedly stacking the negative electrodes of the present application, and the adjacent negative electrodes are separated by an ion liquid retaining layer (the ellipsis in the figure represents a single polarity pole piece not shown). The positive electrode group and the negative electrode group are collectively referred to as the electrode group.

[0094] As an implementation method, Figure 3 As shown, the electrode group is formed by a plurality of unipolar pole pieces 200 repeatedly stacked along the thickness direction X, wherein the first surface of each unipolar pole piece 200 is provided with an ion liquid retaining layer 12, and between two adjacent unipolar pole pieces 200, the second surface of one pole piece is in contact with the ion liquid retaining layer 12 of the other pole piece.

[0095] The battery cell of the present application has a special stacked core structure, which can replace the traditional battery stacked core structure (such as Figure 5 As shown, with a single-layer positive electrode 2a-single-layer separator 30-single-layer negative electrode 1a-single-layer separator 30 as the basic unit, the ellipsis represents the basic unit not shown), the number of collectors and separator layers is saved, so that the proportion of active materials in a certain space is increased, thereby effectively improving the energy density and obtaining a high-rate battery.

[0096] In some embodiments, Figure 4 As shown, the battery cell 100 has a parallel tab structure, that is, each basic unit has a layer of tabs, which is beneficial to reduce the electron conduction path and reduce the resistivity. Figure 3 As shown, the monopolar pole pieces 200 are stacked to form an electrode group, and the pole pieces are separated by ion retaining layers 12. The ion retaining layers 12 play a role in replenishing lithium and eliminate the concentration difference of ions transferred between the positive and negative electrodes.

[0097] In the present application, the number of electrodes in the positive electrode group and the negative electrode group can be set according to the required capacity of the battery. According to some embodiments, the number of positive electrodes in the positive electrode group is n1, 1<n1<272; preferably 180<n1<240, and the number of negative electrodes in the negative electrode group is n2, 1<n2<270, preferably 110<n2<200.

[0098] In the present application, specific examples of the diaphragm include, but are not limited to, PP diaphragm and PE diaphragm.

[0099] In a fourth aspect, the present application provides a method for preparing the battery cell according to the third aspect of the present application, comprising:

[0100] Stacking and hot pressing: The single-polarity pole pieces are stacked by lamination and hot-pressed to form positive and negative electrode groups respectively;

[0101] Separator coating: coating the outer periphery of the positive electrode group and the negative electrode group with a layer of separator respectively;

[0102] Core hot pressing: The positive electrode group coated with the separator and the negative electrode group coated with the separator are stacked and hot pressed.

[0103] In some embodiments, the preparation method further comprises the step of preparing the unipolar pole piece described in the first aspect of the present application. According to a specific embodiment, the process flow of the preparation method is as follows: Figure 8 As shown, specifically including:

[0104] Preparation of ceramic slurry and electrode slurry;

[0105] An electrode coating (primer coating: dip coating of electrode slurry, roller pressing) is formed on a foam current collector (such as foam metal), and an ion liquid retaining layer (top coating: micro-concave coating of ceramic slurry) is formed on the current collector surface to form a coating layer-ion liquid retaining layer basic unit;

[0106] The current collector forming the coating layer-ion liquid retaining layer is cut (not shown), die-cut to form spaced-arranged pole ears, and then cut to obtain a single pole piece;

[0107] The single pole pieces are stacked and hot-pressed to form an electrode group, the periphery of the electrode group is coated with a glue-coated diaphragm (not shown), and the core is hot-pressed to form a thick electrode high-rate stacked core.

[0108] The specific preparation method of the unipolar pole piece is as described in the second aspect of the present application and will not be repeated here.

[0109] In a fifth aspect, the present application provides a secondary battery, the secondary battery comprising the battery cell described in the third aspect of the present application. The secondary battery is a thick electrode high rate battery.

[0110] In some embodiments, the secondary battery is a lithium-ion battery. Generally, the battery core can be placed in a shell, baked, and injected with liquid to obtain a lithium-ion battery.

[0111] In particular, the secondary battery can also be a pseudo-solid lithium battery. Due to the provision of an ion liquid retaining layer, the secondary battery of the present application improves the electrolyte absorption and liquid retention performance, and can significantly reduce the amount of free electrolyte in the battery compared to batteries of the same specifications prepared with traditional pole pieces.

[0112] The following describes embodiments of the present application. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application.

[0113] In the following examples and comparative examples, the preparation methods of the positive electrode slurry, negative electrode slurry, ceramic slurry and electrolyte used are as follows.

[0114] Positive electrode slurry: lithium iron phosphate, conductive agent CNT, dispersant PVP, binder PVDF and solvent NMP were placed in a double planetary mixer at a mass ratio of 96.5:1.3:0.2:2:23, and stirred and dispersed for 6 hours to obtain positive electrode slurry.

[0115] Negative electrode slurry: graphite, conductive agent SP, dispersant CMC, binder SBR and solvent water in a mass ratio of 96.5:1.0:1.5:1.5:72 were placed in a double planetary mixer and stirred and dispersed for 4.5 hours to obtain negative electrode slurry.

[0116] Ceramic slurry: Place nano-ceramic powder, binder PVDF, conductive agent SP and solvent NMP in a ceramic glue making tank at a mass ratio of 20:6:4:70 for stirring and making glue, and control the viscosity at 1000-2000mPa·s to obtain ceramic slurry; wherein the ceramic powders used are aluminum oxide and lithium aluminate, and the mass ratio of the two is 10:3.

[0117] Electrolyte: The solvent is composed of EC:PC:EMC:DMC in a weight ratio of 25:5:50:20, and the electrolyte is LiPF6, with a concentration of 12.5wt% in the electrolyte.

[0118] In the following examples and comparative examples, the prepared batteries are all LFP71173207P-280Ah square aluminum shell lithium iron phosphate energy storage batteries, wherein:

[0119] Comparative Example 1 adopts conventional surface density coating and normal lamination process (the method is shown below), wherein the positive electrode coating surface density is 324g / m 2 In comparative example 2, the positive electrode coating surface density is increased to 530 g / m 2 In the comparative examples, aluminum foil and copper foil were used as positive and negative electrode current collectors, respectively.

[0120] Example 1: A battery is prepared by laminating the positive electrode and the negative electrode of the present application. The surface density of the positive electrode coating is set to 328 g / m 2 The negative electrode coating surface density is 160g / m 2 The compaction density of the positive electrode coating is 2.4g / cm 3 The compaction density of the negative electrode coating is 1.55g / cm 3 , select foamed aluminum and foamed copper with a porosity of 90% and a pore size of 0.05 mm as the positive and negative current collectors respectively. The thickness of the current collector is designed according to the surface density and compaction density (foamed aluminum: 328 / 2.4 / 0.9 = 152 (μm), foamed copper: 160 / 1.55 / 0.9 = 114 (μm)). The thickness of the ion liquid retention layer is 6 μm.

[0121] The main design parameters of Comparative Examples 1-2 and Example 1 are as follows:

[0122] Table 1

[0123]

[0124] Example 1

[0125] (1) Preparation of electrode coating

[0126] Using aluminum foam as the substrate, the positive electrode slurry is coated on the aluminum foam by dip coating to ensure that the slurry fills the pores. After coating, roller pressing is performed. After rolling, a certain area of ​​the electrode is cut off and weighed (target weight of the electrode per unit volume = 90% × 2.4 × 0.0152 + 2.7 × 0.0152 × 10% = 0.0370 (g / cm 3 )), if the electrode sheet does not reach the required value, it needs to be coated again and then rolled, and this process is repeated until the surface density of the current collector reaches the required value to obtain a positive electrode composite current collector;

[0127] Using foam copper as the substrate, the negative electrode slurry is coated by dip coating to ensure that the slurry fills the holes. After coating, it is rolled. After rolling, a certain area of ​​the electrode is cut off and weighed (target weight of the electrode per unit volume = 90% × 1.55 × 0.0114 + 8.7 × 0.0114 × 10% = 0.0258 (g / cm 3 )), if the electrode sheet does not reach the required value, it needs to be coated again and then rolled, and this process is repeated until the surface density of the current collector reaches the required value to obtain a negative electrode composite current collector;

[0128] (2) Preparation of ion-retaining layer

[0129] The ceramic slurry is coated on the surface of the positive electrode composite current collector and the negative electrode composite current collector respectively by using a micro-concave roller, and dried to form an ion liquid retaining layer to obtain a positive electrode and a negative electrode.

[0130] (3) Preparation of battery cells

[0131] A stacking machine is used to stack a single positive electrode and a single positive electrode as the base cycle unit to form a positive electrode group and a negative electrode group according to the designed thickness shown in Table 1, and then the positive electrode group and the negative electrode group are stacked together and hot-pressed to form a battery cell.

[0132] (4) Assembling the battery

[0133] The battery is assembled into a shell, baked, filled with liquid and chemically divided into capacities to obtain a battery.

[0134] Comparative Examples 1-2

[0135] The positive electrode slurry was coated on an aluminum foil with a thickness of 14 μm, dried and cold pressed to form a positive electrode sheet. The negative electrode slurry was coated on a copper foil with a thickness of 8 μm, dried and cold pressed to form a negative electrode sheet.

[0136] Diaphragm: PE+PVDF coated diaphragm (14μm+2μm);

[0137] According to the design shown in Table 1, the positive electrode sheet, the negative electrode sheet and the separator are made into a laminated battery cell through a lamination process, and the battery cell is assembled into a shell, baked, liquid-filled and chemically divided into capacities to obtain a battery.

[0138] Test Case

[0139] 1. Capacity test

[0140] At room temperature, charge to 3.65V with 0.5C constant current and constant voltage, leave for 5 minutes, and then discharge to 2.5V with 0.5C constant current. Calculate the constant current discharge capacity. Test 50 samples in each group to obtain the 0.5C capacity distribution and capacity average.

[0141] The gram capacity is the 0.5C capacity divided by the weight of the active material in the corresponding positive electrode of the battery.

[0142] 2. Internal resistance test

[0143] At room temperature, the internal resistance of the battery was tested using a six-bit half-cell internal resistance tester. 50 samples were tested in each group to obtain the internal resistance distribution and the average internal resistance.

[0144] 3. Battery rate performance test

[0145] At room temperature, charge to 3.65V with 1C, 1.5C, 4C, and 5C constant current and constant voltage respectively, leave for 5 minutes, and then discharge to 2.5V with 0.33C constant current. Calculate the capacity retention rate = discharge capacity of the battery fully charged at other rates and then discharged at 0.33C / (0.33C charging capacity / 0.33C discharging capacity)×100%. Test 5PCS samples in each group and take the average value.

[0146] 4. Battery cycle performance test

[0147] At room temperature, charge to 3.65V with 1C constant current and constant voltage, leave for 5 minutes, then discharge to 2.5V with 1C constant current, leave for 5 minutes, record the discharge capacity, repeat the above steps, the first discharge capacity is recorded as C1, and the nth discharge capacity is recorded as Cn. The cycle capacity retention rate is = C1 / Cn×100%. Test 5PCS samples in each group and take the average value.

[0148] The capacity, gram capacity and internal resistance test results are shown in Table 2, the rate test results are shown in Table 3, and the cycle performance test results are shown in Table 4.

[0149] Table 2

[0150]

[0151] Combining Table 1 and Table 2, it can be seen that in terms of design capacity, the design capacity of Comparative Example 2 and Example 1 is close, both of which are 6% to 7% more than the design capacity of Comparative Example 1; in terms of actual capacity, Example 1>Comparative Example 2>Comparative Example 1, but only the capacity of Example 1 and Comparative Example 1 meets the design requirements, the actual capacity of Comparative Example 2 is lower than the design capacity, and the capacity distribution dispersion is too large; in terms of gram capacity, Example 1≈Comparative Example 1>Comparative Example 2, and the dispersion of Comparative Example 2 is too large. In terms of internal resistance, Example 1<Comparative Example 1<Comparative Example 2, and the dispersion of Comparative Example 2 is too large.

[0152] In summary, the capacity of the lithium battery prepared in Example 1 is increased by about 6% compared with that in Comparative Example 1. Although Comparative Example 2 increases the design capacity by increasing the surface density, the actual gram capacity is low, the internal resistance is large, and the dispersion is very large. The reason may be that the surface density is too high, resulting in poor consistency in the thickness direction of the electrode.

[0153] Table 3

[0154]

[0155] Table 4

[0156]

[0157] Note: In Table 4, week refers to the number of cycles.

[0158] Combining Table 3 and Table 4, it can be seen that in terms of rate performance, the discharge performance of Comparative Example 1 is close to that of Example 1 at 1C-5C, and the rate performance of Comparative Example 2 drops sharply when the discharge rate is greater than 1.5C.

[0159] In terms of cycle life, Example 1 has a slightly higher cycle capacity than Comparative Example 1 at 3000 times, while Comparative Example 2 terminates at about 300 cycles (it is generally believed in the industry that the cycle life terminates when the capacity retention rate is ≤70%).

[0160] Combined with the above results, it can be seen that the battery prepared in Example 1 can maintain a high rate and cycle performance of the battery while improving the battery energy density.

[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A unipolar electrode, which is a positive electrode or a negative electrode, characterized in that: The single-polarity electrode comprises a composite current collector and an ion liquid retaining layer located on the surface of the composite current collector; wherein, The composite current collector comprises a foam current collector and an electrode coating distributed in the pores of the foam current collector, the electrode coating contains an electrode active substance, and the ion liquid retaining layer contains a ceramic material.

2. The monopolar electrode according to claim 1, characterized in that The ion liquid-retaining layer satisfies at least one of the following conditions: (a) Thickness: 1 to 10 μm; (b) the ceramic material is selected from one or more of alumina, boehmite, barium titanate and lithium aluminate; (c) It also includes a conductive agent and a binder, and the mass ratio of the ceramic material, the conductive agent and the binder is 10:(3-8):(2-6).

3. The monopolar electrode according to claim 1 or 2, characterized in that: The foam current collector satisfies at least one of the following conditions: (a) Aperture: 0.001 to 0.1 mm; (b) a porosity of 10% to 95%, preferably 50% to 90%; (c) The thickness is 0.05 to 0.3 mm.

4. The monopolar electrode according to any one of claims 1 to 3, characterized in that: The electrode coating is formed by dipping the foam current collector with an electrode slurry containing the electrode active material and drying the mixture; Preferably, the electrode slurry further contains a conductive agent, a binder and optionally a dispersant.

5. The monopolar electrode according to any one of claims 1 to 4, characterized in that: The monopolar electrode is a positive electrode, and the positive electrode satisfies at least one of the following conditions: (a) The foam current collector is foam aluminum; (b) the electrode active material is selected from at least one of lithium iron phosphate, lithium iron manganese phosphate and lithium nickel cobalt manganese oxide; (c) The surface density of the electrode coating is 200 to 420 g / m 2 ; or, The monopolar electrode is a cathode electrode, and the cathode electrode satisfies at least one of the following conditions: (a) The foam current collector is foam copper; (b) the electrode active material is selected from at least one of graphite, hard carbon and lithium titanate; (c) The surface density of the electrode coating is 100 to 220 g / m 2 .

6. The monopolar electrode according to any one of claims 1 to 5, characterized in that: The monopolar electrode is divided into a pole ear region and a material distribution region, wherein the pole ear region is a pole ear, and the material distribution region has the electrode coating and the ion liquid retention layer.

7. A method for preparing the monopolar electrode according to any one of claims 1 to 6, characterized in that: The method includes: Applying an electrode slurry containing an electrode active material onto a foam current collector so that the pores of the foam current collector are filled with the electrode slurry to form an electrode coating; A ceramic slurry containing the ceramic material is applied on the surface of a current collector forming an electrode coating to form an ion retaining layer.

8. The method according to claim 7, characterized in that The method includes the following steps: The foam current collector is sent to the electrode slurry for dipping by a dip coating machine, and the current collector dipped with the electrode slurry is sent to an oven for drying and rolling to obtain a composite current collector; The ceramic slurry is coated on the surface of the composite current collector by a micro-concave roll coater, and then dried to form an ion liquid retaining layer; Preferably, the method further comprises: Before applying the electrode slurry, one end of the foam current collector is covered with adhesive tape to divide the foam current collector into a tab reserved area covered by the adhesive tape and an area to be laid; After the ion liquid retaining layer is formed, the adhesive paper is removed and the tab reserved area is die-cut to form the tab.

9. A battery cell, characterized in that: It comprises a positive electrode group, a negative electrode group and a separator, wherein the positive electrode group and the negative electrode group are arranged opposite to each other and respectively comprise a plurality of stacked single-polarity pole pieces as described in any one of claims 1 to 6, and adjacent single-polarity pole pieces are separated by an ion liquid-retaining layer; and the outer peripheries of the positive electrode group and the negative electrode group are respectively wrapped with the separator.

10. The battery cell according to claim 9, characterized in that: The number of positive electrodes in the positive electrode group is n1, 1<n1<272; The number of negative electrodes in the negative electrode group is n2, 1<n2<270.

11. A method for preparing the battery cell according to claim 9 or 10, characterized in that: include: Stacking and hot pressing: The single-polarity pole pieces are stacked by lamination and hot-pressed to form positive and negative electrode groups respectively; Separator coating: coating the outermost layers of the positive electrode group and the negative electrode group with a separator respectively; Core hot pressing: The positive electrode group coated with the separator and the negative electrode group coated with the separator are stacked and hot pressed.

12. A secondary battery, characterized in that: include: The battery cell according to claim 9 or 10.

Citation Information

Cited By

  • Negative pole piece, sodium battery and energy storage device

    CN121687854A